Virulence mechanisms of bacterial pathogenes - Brodgen, Kim A (ASM Press, 2000)
The third edition of this widely used reference book provides an overview of current knowledge of the wide variety of mechanisms used by bacterial pathogens in establishing infection, producing disease, and persisting in the host. The overall emphasis is to understand the mechanisms of host–pathogen interactions rather than to focus on specific research approaches. Internationally recognized authorities in the field review ongoing concepts in bacterial invasion, colonization, and survival; bacterial evasion of host defense mechanisms; bacterial effects on host cell function; and identification, regulation, and transfer of virulence genes.
Keywords: bakteriologie